2014
DOI: 10.3892/mmr.2014.2034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets and mechanism of action of dexmedetomidine in treatment of ischemia/reperfusion injury (Review)

Abstract: Abstract. Dexmedetomidine (DEX), a highly specific α 2 -adrenergic agonist, which exhibits anaesthetic-sparing, analgesia and sympatholytic properties. DEX modulates gene expression, channel activation, transmitter release, inflammatory processes and apoptotic and necrotic cell death. It has also been demonstrated to have protective effects in a variety of animal models of ischemia/reperfusion (I/R) injury, including the intestine, myocardial, renal, lung, cerebral and liver. The broad spectrum of biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 92 publications
1
98
0
2
Order By: Relevance
“…In this context, Dex has shown detrimental effects in the myocardium when used as a post-conditioning rather than a pre-conditioning agent [48]. This observation lead Cai et al to hypothesize that the protective effect of Dex depends on timing [10]. Our study may support this idea, since NO is known to be cardioprotective against IR injury [49,50].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this context, Dex has shown detrimental effects in the myocardium when used as a post-conditioning rather than a pre-conditioning agent [48]. This observation lead Cai et al to hypothesize that the protective effect of Dex depends on timing [10]. Our study may support this idea, since NO is known to be cardioprotective against IR injury [49,50].…”
Section: Discussionsupporting
confidence: 80%
“…The modulation of the sympathetic nervous system theoretically maintains the balance in the input/demand relationship of myocardial oxygen. Dex is known to be protective in multiple organs and types of ischemiareperfusion (IR) injury [10]. The mechanism by which it protects may be organspecific.…”
Section: Introductionmentioning
confidence: 99%
“…This is often accompanied by renal ischemia and reperfusion, which affect treatment outcomes (1,2). Therefore, reducing or avoiding IRI is one of the areas in renal protection, which has received significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Since the antagonist atipamezole of the α2-adrenoceptor only partly reversed the neuroprotective effects of dexmedetomidine on neurotoxicity in rats induced by isoflurane, there may be other mechanisms. Several pathways have been reportedly involved in the neuroprotection of dexmedetomidine (Cai et al, 2014;Duan et al, 2014;Liao et al, 2014;Xiong et al, 2014). Li et al (2014) found that dexmedetomidine pretreatment dose-dependently inhibited isofluraneinduced neuroapoptosis by preserving the PI3K/Akt pathway in the hippocampus in neonatal rats.…”
Section: Discussionmentioning
confidence: 99%